1985
DOI: 10.1002/ana.410180510
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis: Immunocytochemical studies of viral antigen and Inflammatory cells in fatal cases

Abstract: The distribution of virus and the composition of the mononuclear inflammatory response were studied in the brains of 7 children who died with Japanese encephalitis. Viral antigen was localized to neurons, with greatest involvement in the thalamus and brainstem. Quantitation of perivascular inflammatory responses showed a preponderance of T cells, but only 7 to 30% of these cells were T suppressor/cytotoxic cells. Inflammatory cells invading the parenchyma were predominantly macrophages with small numbers of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
111
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(130 citation statements)
references
References 22 publications
(3 reference statements)
14
111
1
Order By: Relevance
“…A large number of infected Purkinje and small granule cells were observed in the cerebellum of the macaques, similar to what has been described for humans by Desai and others. 14 However, Johnson and others 12 found no infection of Purkinje cells. The cerebral cortex was less involved in the macaques but considerable antigen was localized in all levels of their spinal cords, especially the ventral horn.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A large number of infected Purkinje and small granule cells were observed in the cerebellum of the macaques, similar to what has been described for humans by Desai and others. 14 However, Johnson and others 12 found no infection of Purkinje cells. The cerebral cortex was less involved in the macaques but considerable antigen was localized in all levels of their spinal cords, especially the ventral horn.…”
Section: Discussionmentioning
confidence: 96%
“…The distribution of JE virus in the brains of macaques experimentally inoculated with JEV duplicates that previously reported in human disease. [12][13][14] In both, the virus distribution in the CNS was disseminated, with the greatest intensity in the thalamus and brain stem. A large number of infected Purkinje and small granule cells were observed in the cerebellum of the macaques, similar to what has been described for humans by Desai and others.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Approximately half of the survivors suffer from permanent neurological and/or mental impairment due to the invasion and destruction of the cortical neurons and Purkinje cells by the virus (30,37). Several species of Culex mosquitoes are responsible for transmission of the virus to humans after the ingestion of blood meals from viremic birds or mammals.…”
mentioning
confidence: 99%
“…Studies of neurotropism in a hamster model of St. Louis encephalitis virus infection have shown the importance of axonal transport through olfactory neurons (Monath et al, 1983), thus evading the blood brain barrier. However, postmortem studies on patients who died from Japanese encephalitis virus infection showed diffuse infection throughout the brain, indicating a hematogenous route of entry (Desai et al, 1995;Johnson et al, 1985). Infection of parenchyma may therefore result from either simple diffusion from vascular endothelial cells at sites where the integrity of the blood brain barrier has been compromised due to trauma, or through replication of the virus in the endothelial cells of brain capillaries, and release of the virus into the brain.…”
Section: Pathogenesis and Clinical Featuresmentioning
confidence: 99%